Comparison of the Effects of Sesame Oil and Oleic Acid as Suspension Vehicles on Gastrointestinal Absorption of Phenytoin in Rats - YAMANAKA, YOU; MIZUNO, NOBUYASU; HAMAGUCHI, TSUNEO; SHINKUMA, DENJI; YATA, NOBORU (Chemical & pharmaceutical bulletin, 1985)
The bioavailabilities of phenytoin (DPH) from oil suspensions (sesame oil and oleic acid) were studied in rats in relation to the physicochemical properties and gastric emptying time of the vehicles. The maximum blood concentration (Cmax) of DPH after oral administration of sesame oil suspension was about twice that from the oleic acid suspension. DPH in oleic acid suspension was absorbed more slowly ; this was consistent with the dissolution rate data. Oleic acid delayed gastric emptying to a significant degree in comparison with sesame oil. The area under the blood concentration-time curve (AUC) for the oleic acid suspension was significantly higher than that for the sesame oil suspension. On the other hand, AUC and blood concentrations of DPH after intraduodenal administration of oleic acid suspension were approximately twice those obtained with the sesame oil suspension up to one hour after administration. It was concluded that the lower Cmax of DPH, the higher AUC and the longer Tmax (the time required to reach the maximum blood concentration) after oral administration of oleic acid suspension as compared with those in the case of sesame oil suspension could be attributed to the delayed gastric emptying.